2013
DOI: 10.1021/mz300669q
|View full text |Cite
|
Sign up to set email alerts
|

High Density Polymer Brush Spontaneously Formed by the Segregation of Amphiphilic Diblock Copolymers to the Polymer/Water Interface

Abstract: A self-repairable high density polymer brush of poly(ethylene glycol) (PEG) is formed at the interface between cross-linked poly(dimethyl siloxane) (PDMS) and water by spontaneous surface segregation of an amphiphilic diblock copolymer consisting of PEG and PDMS. The surface reconstruction by the formation of the brush was observed as the large hysteresis of the contact angle of the water droplet. Neutron reflectivity measurement revealed that the grafting density of the polymer brush is 2.8 chain/ nm 2 , whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 30 publications
1
82
0
1
Order By: Relevance
“…The osmotic pressure in the PAA(6.1) (Π sum = 25.4 MPa) is ≈9 MPa higher than in the PEG(2.1) brush (Π sum = 16.3 MPa), despite the fact that the modeled grafting density is higher for PEG(2.1) ( σ = 2.52 chains nm −2 ) than for PAA(6.1) ( σ = 1.39 chains nm −2 ). The predicted σ = 2.52 chains nm −2 for PEG(2.1) according to this model was very close to the experimentally determined value σ = 2.8 chains nm −2 by Inutsuka et al [ 22 ] for the same size PEG block segregated into water from PDMS matrix, which supports the validity of the presently proposed model for segregation. See Table 1 for calculated H , φ , σ , and Π at minimum Δ F total at different pH for the block copolymers.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The osmotic pressure in the PAA(6.1) (Π sum = 25.4 MPa) is ≈9 MPa higher than in the PEG(2.1) brush (Π sum = 16.3 MPa), despite the fact that the modeled grafting density is higher for PEG(2.1) ( σ = 2.52 chains nm −2 ) than for PAA(6.1) ( σ = 1.39 chains nm −2 ). The predicted σ = 2.52 chains nm −2 for PEG(2.1) according to this model was very close to the experimentally determined value σ = 2.8 chains nm −2 by Inutsuka et al [ 22 ] for the same size PEG block segregated into water from PDMS matrix, which supports the validity of the presently proposed model for segregation. See Table 1 for calculated H , φ , σ , and Π at minimum Δ F total at different pH for the block copolymers.…”
Section: Discussionsupporting
confidence: 89%
“…Interfaces 2016, 3, 1500472 www.advmatinterfaces.de www.MaterialsViews.com The main driving force of the segregation of hydrophilic chains from PDMS matrix is facile solvation of polymer chains in solvent that is interfacing with PDMS surface. Recently, Inutsuka et al [ 22 ] have also shown a spontaneous formation of PEG brushes from PDMS(1.0)-b -PEG(2.1) at the interface between PDMS and water via segregation from PDMS network. We consider that the same mechanism governs the distribution of the PDMS(5.0)-b -PEG(2.1) copolymers within the PDMS matrix in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This PDMS thin film incorporating diblock copolymers can be deposited on various materials' surfaces. Upon exposure to water [4], or often after applying initiating tribostress in water, hydrophilic blocks (PAA) of the copolymers are selectively segregated from the PDMS network to form brush-like layers, whereas the hydrophobic blocks (PDMS) remain trapped inside the PDMS network acting as anchors for the hydrophilic polymer brushes. Excellent anchoring stability of hydrophilic brush layer is a distinct novelty of this system, indebted from high reluctance of hydrophobic blocks to get exposed to aqueous solution and/or from facile replenishment of the diblock copolymers in case of film damage.…”
Section: Introductionmentioning
confidence: 99%